2015
DOI: 10.1016/j.electacta.2015.03.084
|View full text |Cite
|
Sign up to set email alerts
|

Prussian Green: A High Rate Capacity Cathode for Potassium Ion Batteries

Abstract: The influence of the precursors, namely potassium ferrocyanide and potassium ferricyanide on the particles sizes of Prussian Blue (PB) and Prussian Green (PG), under identical reaction conditions have been investigated. It was found that the particle sizes influence the gravimetric capacity utilization of these materials as cathodes for aqueous potassium (K +) ion batteries. The PG particle sizes were on the order of 50-75 nm, whereas PB particles size were on the order of 2-10 microns. The PG cathodes demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(102 citation statements)
references
References 14 publications
0
101
0
1
Order By: Relevance
“…Indeed Prussian blue analogues have mostly been evaluated as a NIB cathode material before the recent interest in KIBs, after Wessells et al . and Padigi et al . reported very stable cycling of Prussia blue in aqueous electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed Prussian blue analogues have mostly been evaluated as a NIB cathode material before the recent interest in KIBs, after Wessells et al . and Padigi et al . reported very stable cycling of Prussia blue in aqueous electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Aqueous systems, comprising Prussian blue (KFe III Fe II (CN) 6 ) or other hexacyanoferrates as active material, have been studied intensively since the 1980s. [11][12][13][14][15] In addition, * Electrochemical Society Member. z E-mail: daniel.buchholz@kit.edu; stefano.passerini@kit.edu layered K x MnO 2 · (0.3 ≤ y ≤ 0.6) H 2 O has been reported as cathode material in aqueous K-ion capacitors.…”
mentioning
confidence: 99%
“…It indicated that K + intercalation has achieved. Also, the color of the electrode changes from dark gray to golden, which confirms the formation of KC 8 in the electrode …”
Section: Resultsmentioning
confidence: 56%
“…At present, the improvement of the cyclic stability of PIBs graphite‐based anode is a focus of attention. The dramatic volume expansion accompanied by K + insertion‐disinsertion reaction was one of the major causes of poor cycling performance . It is useful to improve the K + intercalation/delamination crystal gap of graphite and to establish an optimized nanostructure based on graphite to buffer the volume change.…”
Section: Introductionmentioning
confidence: 99%